Senecavirus A as an Oncolytic Virus: Prospects, Challenges and Development Directions - Luo, Dankun; Wang, Haiwei; Wang, Qiang; Liang, Wenping; Liu, Bo; Xue, Dongbo; Yang, Yang; Ma, Biao (Frontiers in Oncology, 2022)
Oncolytic viruses have the capacity to selectively kill infected tumor cells and trigger protective immunity. As such, oncolytic virotherapy has become a promising immunotherapy strategy against cancer. A variety of viruses from different families have been proven to have oncolytic potential. Seneca virus A (SVA) was the first oncolytic picornavirus to be tested in humans shown to penetrate solid tumors through the vascular system. SVA has properties that make it a suitable model, such as its inability to integrate into human genome DNA and the lack of any viral-encoded oncogenes. In addition, genetic engineering of SVA based on the manipulation of infectious clones facilitates the development of viruses with improved therapeutic indexes to satisfy the criteria of regulatory safety and efficacy. This review summarizes the current knowledge and strategies of genetic engineering for SVA, and addresses the current challenges and future directions as an oncolytic virus.